The effect of 'smart' financial incentives on driving behaviour of novice drivers. (October 2018) - Mortimer, Duncan; Wijnands, Jasper S.; Harris, Anthony; Tapp, Alan; Stevenson, Mark
Highlights: Penalties for risky driving may be more effective than rewards of equal value. Even low-value incentives can produce reductions in risky driving behaviours. Motivational crowding out is unlikely to negate the impact of low-value incentives. Low-value penalties are likely to be more cost-effective than high-value rewards. Abstract: Recent studies have demonstrated that financial incentives can improve driving behaviour but high-value incentives are unlikely to be cost-effective and attempts to amplify the impact of low-value incentives have so far proven disappointing. The present study provides experimental evidence to inform the design of 'smart' and potentially more cost-effective incentives for safe driving in novice drivers. Study participants (n = 78) were randomised to one of four financial incentives: high-value penalty; low-value penalty; high-value reward; low-value reward; allowing us to compare high-value versus low-value incentives, penalties versus rewards, and to test specific hypotheses regarding motivational crowding out and gain/loss asymmetry. Results suggest that (i) penalties may be more effective than rewards of equal value, (ii) even low-value incentives can deliver net reductions in risky driving behaviours and, (iii) increasing the dollar-value of incentives may not increase their effectiveness. These design principles are currently being used to optimise the design of financial incentives embedded within PAYD insurance, with their impact on the driving behaviour of novice drivers to be evaluated in on-road trials.